Contribution of Noncanonical Splice Variants to TTN Truncating Variant Cardiomyopathy. (October 2021) - Patel, Parth N.; Ito, Kaoru; Willcox, Jon A.L.; Haghighi, Alireza; Jang, Min Young; Gorham, Joshua M.; DePalma, Steven R.; Lam, Lien; McDonough, Barbara; Johnson, Renee; Lakdawala, Neal K.; Roberts, Amy; et al.
Abstract : Background: Heterozygous TTN truncating variants cause 10% to 20% of idiopathic dilated cardiomyopathy (DCM). Although variants which disrupt canonical splice signals (ie, invariant dinucleotide of the splice donor site, invariant dinucleotide of the splice acceptor site) at exon-intron junctions are readily recognized as TTN truncating variants, the effects of other nearby sequence variations on splicing and their contribution to disease is uncertain. Methods: Rare variants of unknown significance located in the splice regions of highly expressed TTN exons from 203 DCM cases, 3329 normal subjects, and clinical variant databases were identified. The effects of these variants on splicing were assessed using an in vitro splice assay. Results: Splice-altering variants of unknown significance were enriched in DCM cases over controls and present in 2% of DCM patients ( P =0.002). Application of this method to clinical variant databases demonstrated 20% of similar variants of unknown significance in TTN splice regions affect splicing. Noncanonical splice-altering variants were most frequently located at position +5 of the donor site ( P =4.4×10 7 ) and position -3 of the acceptor site ( P =0.002). SpliceAI, an emerging in silico prediction tool, had a high positive predictive value (86%–95%) but poor sensitivity (15%–50%) for the detection of splice-altering variants. Alternate exons spliced out of most TTN transcripts frequently lacked the consensus base at +5 donor and −3 acceptor positions. Conclusions: Noncanonical splice-altering variants in TTN explain 1-2% of DCM and offer a 10-20% increase in the diagnostic power of TTN sequencing in this disease. These data suggest rules that may improve efforts to detect splice-altering variants in other genes and may explain the low percent splicing observed for many alternate TTN exons. Abstract : Supplemental Digital Content is available in the text.